Concurrent IDH1 and SMARCB1 Mutations in Pediatric Medulloblastoma: A Case Report - El-Ayadi, Moatasem; Egervari, Kristof; Merkler, Doron; McKee, Thomas A.; Gumy-Pause, Fabienne; Stichel, Damian; Capper, David; Pietsch, Torsten; Ansari, Marc; von Bueren, André O. (Frontiers in Neurology, 2018)
Isocitrate Dehydrogenase-1 (IDH1) is a driver gene in several cancers including brain tumors such as low-grade and high-grade gliomas. Mutations of SMARCB1 were described in atypical teratoid rhabdoid tumors and to date have not been associated with the pathogenesis of medulloblastoma. We report concurrent IDH1 and SMARCB1 mutations in a medulloblastoma patient. We searched the catalogue of somatic mutations in cancer (COSMIC) database and other mutation databases and -to our knowledge- this is the first reported case of medulloblastoma harboring both mutations together. Our patient is a thirteen-year-old male presenting with headache and vomiting at diagnosis. MRI revealed left cerebellar expansive lesion with no evidence of metastasis. A histopathological diagnosis of desmoplastic/nodular medulloblastoma was made after complete resection of the tumor. Immunophenotypic characterization and methylation profiling suggested a medulloblastoma with SHH activation. Next generation sequencing of a panel of 400 genes revealed heterozygous somatic IDH1(p.R132C), SMARCB1(p.R201Q), and CDH11(p.L625T) mutations. The patient was treated according to the HIT-SIOP PNET 4 protocol. He is in complete remission more than two years after diagnosis. In conclusion, increasing use of high throughput sequencing will certainly increase the frequency with which rare mutations or mutation combinations are identified. The exact frequency of this mutation combination and whether it has any particular therapeutic implications or prognostic relevance requires further investigation.